Development of a separation system using 3D dielectrophoretic well - 299842 Mohd. Azhar Abdul Razak; Labeed, Fatima, supervisor; Hughes, Michael P., supervisor; School of Engineering (2013)
Thesis (Ph.D) - University of Surrey, 2013